Learning curve analysis of transapical NeoChord mitral valve repair. (21st February 2018) - Colli, Andrea; Bagozzi, Lorenzo; Banchelli, Federico; Besola, Laura; Bizzotto, Eleonora; Pradegan, Nicola; Fiocco, Alessandro; Manzan, Erica; Zucchetta, Fabio; Bellu, Roberto; Pittarello, Demetrio; Gerosa, Gino
Abstract: OBJECTIVES: Transapical off-pump mitral valve intervention with neochordae implantation is a novel, minimally invasive procedure for treatment of degenerative mitral valve regurgitation. The aim of this study was to apply control charts (CUSUM curves) to monitor the performance of NeoChord repair during the initial phase of its adoption. METHODS: The first 112 consecutive patients who underwent NeoChord repair at our institution between November 2013 and March 2016 were included in the analysis. Mitral Valve Academic Research Consortium criteria for 1-year patient success was utilized to determine failed procedures. Control charts had predetermined acceptable and unacceptable failure rates of 5% and 15%, respectively. RESULTS: The actual incidence of 1-year-patient failure was 11% (12 of 112 cases), with a cluster of failures within the first 20 cases. The CUSUM analysis demonstrated an initial learning curve; however, the upper boundary (alarm line) was never crossed. The reassurance line was first crossed after 40 procedures and performance remained stable after 49 procedures. CONCLUSIONS: NeoChord repair is a safe procedure, and the results are maintained through the 1-year follow-up. A relative high number of implants were required to overcome the learning curve at our institution due to the concurrent development of patient selection criteria and the technical refinement of the procedure. Future studies are needed to assess the evolution of the learning curve after the wide adoption of the procedure across European and North American centres.